2022
DOI: 10.1111/nph.17961
|View full text |Cite
|
Sign up to set email alerts
|

An aspartic protease 47 causes quantitative recessive resistance to rice black‐streaked dwarf virus disease and southern rice black‐streaked dwarf virus disease

Abstract: Summary Rice black‐streaked dwarf virus disease (RBSDVD) and southern rice black‐streaked dwarf virus disease (SRBSDVD) are the most destructive viral diseases in rice. Progress is limited in breeding due to lack of resistance resource and inadequate knowledge on the underlying functional gene. Using genome‐wide association study (GWAS), linkage disequilibrium (LD) decay analyses, RNA‐sequencing, and genome editing, we identified a highly RBSDVD‐resistant variety and its first functional gene. A highly RBSDV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…RDV‐borne N. cincticeps were collected from Zhejiang Province, China and maintained under experimental conditions for over 10 generations. Nonviruliferous S. furcifera or N. lugens nymphs were reared on SRBSDV‐infected or RRSV‐infected rice plants for 7 days and then transferred onto healthy rice seedlings for 8 days to allow the virus to pass through its circulation period before being used for virus transmission (Wang, Zhou et al ., 2022 ; Zhang et al ., 2018 ). The RGDV‐borne strain of R. dorsalis was established as described previously (Chen et al ., 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…RDV‐borne N. cincticeps were collected from Zhejiang Province, China and maintained under experimental conditions for over 10 generations. Nonviruliferous S. furcifera or N. lugens nymphs were reared on SRBSDV‐infected or RRSV‐infected rice plants for 7 days and then transferred onto healthy rice seedlings for 8 days to allow the virus to pass through its circulation period before being used for virus transmission (Wang, Zhou et al ., 2022 ; Zhang et al ., 2018 ). The RGDV‐borne strain of R. dorsalis was established as described previously (Chen et al ., 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…The ability of the virus to successfully infect susceptible hosts depends on the presence of proviral host factors and resources in the hosts necessary for its infection and movement. 74 Wang et al 75 showed that the rice aspartate protease 47 (OsAP47) could negatively regulate plant resistance to SRBSDV, and the OsAP47 overexpressing plants were more susceptible to SRBSDV infection, while knockout mutants showed noticeably higher resistance. 75 Nuclear factor Y (NF-Y) transcription factors (TFs) are important in rice growth and development, and can inhibit plant resistance to viruses.…”
Section: Host Genes In Response To Srbsdv Infestationmentioning
confidence: 99%
“…74 Wang et al 75 showed that the rice aspartate protease 47 (OsAP47) could negatively regulate plant resistance to SRBSDV, and the OsAP47 overexpressing plants were more susceptible to SRBSDV infection, while knockout mutants showed noticeably higher resistance. 75 Nuclear factor Y (NF-Y) transcription factors (TFs) are important in rice growth and development, and can inhibit plant resistance to viruses. Tan et al 76 found a negative role of the rice NF-YA gene family against SRBSDV.…”
Section: Host Genes In Response To Srbsdv Infestationmentioning
confidence: 99%
“…Further haplotype analyses suggested that a candidate gene LOC_Os06g03150 is mainly associated with the differentiation of resistance within the Xian subgroup and LOC_Os06g31190 mainly explained the difference in the resistance between Xian and Geng . Using genome-wide association study (GWAS), linkage disequilibrium (LD) decay analyses, RNA-sequencing, and genome editing, a highly RBSDV-resistant variety and its first functional gene, Hap1, was identified [ 140 ]. Besides, multiple recessive resistance loci to RYMV have been mapped [ 141 , 142 ].…”
Section: The Complex Interactions Between Rice Viruses and Their Hostsmentioning
confidence: 99%